Neuromuscular differences of selected and non-selected Iraqi National Soccer players - Rumpf, M. C.; Rodriguez, G. (Journal of Human Sport & Exercise, 2018)
Background: The purpose was to investigate anthropometric, neuromuscular and physiological differences between selected and non-selected Iraqi National soccer players in their preparation to the Olympic Games 2016. Methods: A total of 32 players (selected (N=16) and non-selected (N=16)) participated on three separate training camps. Each occasion was separated by four month and the following performances were measured: Cooper Test, countermovement jump with (CMJ) and without arms (SJ). The data collection was part of the national monitoring process of the U23-Iraq National Soccer team for their preparation for the Olympic Games 2016. All data were analyzed with independent t-tests for each occasion. Results: Selected players had significant higher SJ performance on the first testing and significant higher CMJ performance compared to non-selected players on every testing occasion. However, non-selected players had significant higher cooper-test performance for the first and second test occasion. Conclusion: It seems that neuromuscular performance such as the SJ and CMJ test separates selected U23-Iraqi National soccer players from their non-selected counterparts. Aerobic endurance capacity did not seem to be critical in the selection process.